Quantitative X-ray diffraction phase analysis of poorly ordered nontronite clay in nickel laterites - Wang, Xiaodong; Li, J.; Hart, Robert; Van Riessen, Arie; McDonald, R. (BLACKWELL PUBLISHING, 2011)
Studies of the extraction of nickel from low-grade laterite ores require a much better quantitative understanding of the poorly ordered mineral phases present, including turbostratically disordered nontronite. Whole pattern refinements with nontronite X-ray diffraction data from a Western Australian nickel deposit (Bulong) using a nontronite lattice model (Pawley phase) with two space groups(P3 and C2/m) and a peaks phase group model were performed to improve the accuracy of quantitative X-ray diffraction of nickel laterite ore samples. Modifications were applied when building the new models to accommodate asymmetric peak shape and anisotropic peak broadening due to the turbostraticdisorder. Spherical harmonics were used as convolution factors to represent anisotropic crystal size and strain and asymmetric peak shape when using the lattice model. A peaks phase group model was also developed to fit the anisotropic peak broadening in the nontronite pattern. The quantitative resultsof the new Pawley phase and peaks phase group models were compared and verified with synthetic mixtures of nontronite, quartz and goethite simulating various West Australian laterite ore compositions. The models developed in this paper demonstrate adequate accuracy for quantification of nontronite in the synthesized reference materials and should be generally applicable toquantitative phase analysis of nontronite in nickel laterite ore samples.